PENGARUH PARKIR PADA JALAN TERHADAP KINERJA RUAS JALAN ABUL HASAN DI KOTA SAMARINDA - JUNAIDI, JUNA (KURVA S JURNAL MAHASISWA, 2014)
Junaidi , technique faculty, study program civil faculty, 17 august 1945 Samarinda University. Research tittle “ Park effect  at Road  body about procedure Abul  Hasan  space  road  in Samarinda  city “. This thesis under guidance Ir. Yohanes Nono Juwono MT  as counselor I and Sahrullah , ST, MT as counselor II.Traffic jam  which  caused by shop matters activity indirect have impact to transportation  problem  many of  vehicle which parking, but less of  suitable parking area  so still found park at border road, so often  caused  traffic jam in  this road.The purpose of this thesis writing is to know par k effect  level  at Abul Hasan  road body  in Samarinda  city. Substance of  this thesis as condition graduate BA Degree  in 17 August  1945 University  in Samarinda. As information  substance  for next researcher especially which related  with  traffic jam and park density at Abul Hasan road body in Samarinda  City.From data of result research  based on calculation  by park existence in road body in this space influence vehicle speed. It seen from speed descent  which should more than 45 km/hour (<45km /hour) become 17.234 km/hour .Based on research result hoped at busy hours reduce beside obstacle, because with high beside obstacle will reduce vehicle speed and make density increase so occur adjournment or jamming also reduce road capacity  and servicing level in Abul Hasan road space. Expected any park facility that large enough so that nothing vehicle that park in road body caused school and shop matter activity.